2019
DOI: 10.1080/0886022x.2019.1635893
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin and diabetes are independently related with soluble transferrin receptor levels in chronic dialysis patients

Abstract: Background: Soluble transferrin receptor (sTfR) is a biomarker of erythropoiesis, which is often impaired in dialysis patients. The aim of our study was to evaluate sTfR levels in chronically dialyzed patients and assess potential determinants of its levels. Methods: We performed a cross-sectional study by evaluating 246 end-stage renal disease patients undergoing dialysis and 32 healthy controls. Circulating levels of interleukin (IL)-6, C-reactive protein (CRP), tumor necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
1
8
2
2
Order By: Relevance
“…sTfR is a dimeric protein present in serum, which is a part of the transferrin receptor after enzymatic cleavage [58]. In the study of Belo et al [59], sTfR values were higher in hemodialyzed diabetic patients when compared to hemodialyzed non-diabetic patients and were significantly correlated with circulating iron, ferritin, transferrin saturation, hepcidin, MCH, and MCHC. There were no statistically significant differences in GDF-15 and hepcidin between diabetic and non-diabetic patients who were on hemodialysis in their study.…”
Section: Discussionmentioning
confidence: 98%
“…sTfR is a dimeric protein present in serum, which is a part of the transferrin receptor after enzymatic cleavage [58]. In the study of Belo et al [59], sTfR values were higher in hemodialyzed diabetic patients when compared to hemodialyzed non-diabetic patients and were significantly correlated with circulating iron, ferritin, transferrin saturation, hepcidin, MCH, and MCHC. There were no statistically significant differences in GDF-15 and hepcidin between diabetic and non-diabetic patients who were on hemodialysis in their study.…”
Section: Discussionmentioning
confidence: 98%
“…рТФР -продукт протеолиза рецептора в определенном сайте внеклеточного домена. Отщепленные мономеры рТФР могут быть определены в плазме или сыворотке [36,37].…”
Section: Discussionunclassified
“…Исследования, направленные на оценку рТФР при СД [36,37], представлены в мировой литературе ограниченно, а работ, целью которых являлось бы установление чувствительности и специфичности указанного маркера в отношении ЖДА именно для когорты пациентов с СД, не представлено вообще.…”
Section: Discussionunclassified
“…Hepcidin is also important for innate immunity (22). In chronic inflammatory status, enhanced serum hepcidin synthesis has been correlated with increased interleukin-6 and CRP (23). Previous studies showed that dialysis patients had higher levels of serum hepcidin compared to general population, possibly due to impaired renal excretion, chronic inflammatory status, iron administration, ESA dose, and inadequate dialysis (24,25).…”
Section: Discussionmentioning
confidence: 99%